IRDIS, the dual-band imager camera of SPHERE: testing the performances in laboratory. Issue Volume 8:Issue S299(2013) (6th January 2014) - Zurlo, A.; Vigan, A.; Moutou, C.; Mesa, D.; Gratton, R.; Langlois, M.; Beuzit, J.-L.; Costille, A.; Desidera, S.; Dolhen, K.; Gry, C.; Madec, F.; et al.
Abstract: Next year the second generation instrument SPHERE will begin science operations at the Very Large Telecope (ESO). This instrument will be dedicated to the search for exoplanets through the direct imaging techniques, with the new generation extreme adaptive optics. In this poster, we present the performances of one of the focal instruments, the Infra-Red Dual-beam Imaging and Spectroscopy (IRDIS). All the results have been obtained with tests in laboratory, simulating the observing conditions in Paranal. We tested several configurations using the sub-system Integral Field Spectrograph (IFS) in parallel and simulating long coronographic exposures on a star, calibrating instrumental ghosts, checking the performance of the adaptive optics system and reducing data with the consortium pipeline. The contrast one can reach with IRDIS is of the order of 10 −6 at 0.5 arcsec separation from the central star.